MORE THAN MEETS THE EYE: WHAT PROVERBS MEAN IN THE THEOLOGICAL WORKS OF EMANUEL SWEDENBORG - Petrova, Roumyana (Proverbium - Yearbook, 2020)
This study presents twenty five cases of semantic comparison that demonstrate the similarity between a text fragment from the translatеd theological works of the world-renowned Swedish scientist, engineer, philosopher and mystic Emanuel Swedenborg (1688-1772) and its corresponding proverb or phrase (e.g., virtue is its own reward, truth will out, love is blind, my better half, a stumbling block, etc.). Some conclusions regarding the possible origin of such proverbs and phrases are suggested resting on the results of this analysis.